Ontogenesis peculiarities species of genus Rorippa Scopoli (Cruciferae) in the subzone of the southern taiga - Shabalkina S. (Zenodo, 2014)
Latent, pregenerative and generative periods in the ontogeny of Rorippa amphibia (L.) Bess., R. palustris (L.) Bess. and R. ×anceps (Wahlenb.) Reichenb. were described. Skipping of a postgenerative stage, and some of ontogenetic states demonstrates the dynamic multiplicity of individual development; while the combination of seed and vegetative reproductions – multiplicity of the ways of reproduction and generation. The ontogeny of R. palustris individuals corresponds to A-type, R. amphibia and R. ×anceps – to G-type, and R. ×anceps – to D-type.